Nilai-Nilai Akhlak Dalam Hubungan Edukatif Guru Dan Murid Perspektif Al-Ghazali Dan Al-Zarnuji Serta Relevansinya Terhadap Pendidikan Islam Kontemporer - Sulaiman (Scientific Journal for Nation Building, 2026)
This study aims to examine the concept of morality in teacher–student interactions from the perspectives of Imam Al-Ghazali and Shaykh Burhanuddin Al-Zarnuji, as well as its relevance to the development of contemporary Islamic education. This research employs a qualitative approach using library research by examining Al-Ghazali’s major works, namely Ihya’ ‘Ulum al-Din and Bidayat al-Hidayah, as well as Al-Zarnuji’s Ta‘lim al-Muta‘allim Tariq al-Ta‘allum, supported by various related scholarly sources. The data were analyzed using content analysis through the processes of identifying, classifying, and comparing the educational concepts of both scholars. The findings reveal that Al-Ghazali and Al-Zarnuji equally regard morality and proper conduct as the fundamental foundations of educational success. Al-Ghazali emphasizes spiritual dimensions through the purification of the soul (tazkiyat al-nafs), educators’ exemplary conduct, sincerity, and character formation, while Al-Zarnuji places greater emphasis on practical ethics in seeking knowledge, such as intention, respect for teachers, discipline, and perseverance in learning. Their ideas complement each other in developing an Islamic educational system that integrates intellectual, moral, and spiritual dimensions. The relevance of their thoughts is reflected in efforts to strengthen students’ character, foster an academic culture, and establish humane teacher–student relationships in modern education.